A investigação defensiva no direito processual penal brasileiro - Kiss, Vanessa Morais (2021)
Since the preliminary investigation is the stage where crucial aspects of the future potential accusation are established, it is extremely important that, from this point on, legal assistance is guaranteed to the person under charges, not only in order to protect their rights on a formal level, but also as to allow the proper and timely preparation of their substantial defense. Based on this premise, part of the doctrine, inspired by foreign law experiences, has proceeded to advocate for the regulation of defensive investigation in Brazil. The prerogative of practicing investigative diligences with the aim of gathering information that may be useful for the defensive strategy, so as to ensure the equality of arms between parts, contributes to amplify the judge’s cognitive space since the preliminary stages of the criminal prosecution, so as to avoid empty accusations or unfounded precautionary measures. It is possible to claim the existence of a right to investigate, once the fulfillment of the right to proof and the effectiveness of the defense depend on the power of autonomously searching and gathering evidence. Although the issue has not yet been settled legally, a few important guidelines have been laid down by Resolution 188/2018, issued by the Federal Board of the Brazilian Bar Association. In addition, the constitutional grounds of the defensive investigation can be inferred from the due process of law clause, as well as from the right to an adversary judgement and to an effective defense. Currently, the possibility of introducing the regulation of the matter in the Code of Criminal Proceedings in under discussion in the National Congress. However, there is a series of obstacles, not only from a legal, but also from an institutional, cultural, and material standpoint, to be overcome in the path to the full assimilation of the institute of investigative defense to the Brazilian legal system, and, specially, to its incorporation to our model of public legal assistance